1968
DOI: 10.5558/tfc44005-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between External Features and Trunk Rot in Living Yellow Birch

Abstract: Although broken bmnches and bqsanch stubs are t h e m o s t frequently encoz~ntered external signs of defects in the t?.unlc of yellozu birch, t h e y zue?.e found t o be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…According to the results of the current research, in all treatments, 97 % of scuff, scrape, and gouges occurred within the fi rst 1.3 m of the bole (Nikooy 2007, Behjou 2014. Other studies have shown that wounds with >100 cm 2 of exposed sapwood are likely to develop decay (Hesterberg 1957, Lavallee andLortie 1968). The frequency of overall damage for the second treatment in this study is higher than those reported in the literature for damage from felling in individual tree selection (2.4 %).…”
Section: Rasprava I Zaključcicontrasting
confidence: 58%
“…According to the results of the current research, in all treatments, 97 % of scuff, scrape, and gouges occurred within the fi rst 1.3 m of the bole (Nikooy 2007, Behjou 2014. Other studies have shown that wounds with >100 cm 2 of exposed sapwood are likely to develop decay (Hesterberg 1957, Lavallee andLortie 1968). The frequency of overall damage for the second treatment in this study is higher than those reported in the literature for damage from felling in individual tree selection (2.4 %).…”
Section: Rasprava I Zaključcicontrasting
confidence: 58%
“…There was an overlap for these data as there is an 80-percent chance that wounds of 130 to 200 square inches will develop decay within 20 years. Lavallee and Lortie (1968) observed similar effects with the removal of only 90 square inches of bark from yellow birch trees. aAverage percent reduction in size of wounds in parentheses.…”
Section: Discussion and Summarymentioning
confidence: 55%
“…Damage is largely confined to saplings and poles, though sawtimber trees also are wounded (Lamson and Miller 1983). Research has shown that exposed sapwood wounds of more than 100 square inches are likely to develop decay (Hesterberg 1957;Lavallee and Lortie 1968). Lamson and Miller (1 983) reported results from stands of pole-and small sawtimber-size trees logged with a rubber-tired skidder on relatively gentle to flat slopes.…”
Section: Introductionmentioning
confidence: 99%
“…These are known to be related to a higher probability of stem mortality (Guillemette et al 2008) and are usually associated with decayed wood (Lavallée and Lortie 1968;Boulet 2007). The effect of fungal infections on tree value increased with stem diameter, probably because larger trees are generally older and contain a greater proportion of decayed wood (Basham 1991).…”
Section: Discussionmentioning
confidence: 99%
“…While the incidence of frost cracks has been associated with larger trees (Burton et al 2008), we did not observe an interaction between cracks and stem diameter in our study. Cracks are often associated with undesirable internal characteristics, such as discoloration or decay (Shigo 1966;Lavallée and Lortie 1968), which in turn may decrease the value of raw material designated for appearance wood products (Wiedenbeck et al 2004).…”
Section: Discussionmentioning
confidence: 99%